The need to reformulate education policy for purposes of addressing religious extremism, with reference to three South African policy documents - Johannes L van der Walt (Comparative Education Society of Iran ( CESIR), 2018)
Religious and other forms of extremism are rife in modern societies. This paper explores some of the reasons why some young people do not follow the "normal" pathways towards becoming citizens who can contribute to the well-being of society and to peaceful coexistence. The answer to this problem seems to lie in the nature of their education as well as in other factors and conditions in their environments. Radicalisation through education gone awry can drive a young person towards extremism. Young people therefore have to be educated in ways that would prevent them from becoming radicalised. This insight should also be reflected in education policy documents. Three South African education policy documents are used to demonstrate how policy documents could be revised to include strategies for the prevention of (religious, cultural and political) extremism, namely the Manifesto on Values, Education and Democracy (2001), the National Policy on Religion Education (2003) and the Curriculum and Assessment Policy Statements (2011).